MEKANISME PENETAPAN HARGA JUAL PRODUK DAN LABA DALAM PANDANGAN EKONOMI ISLAM (Studi Kasus di Minimarket Family Bekasi) - Puti Khairani Rijad; Salma Nur Fadhilah (DIRHAM Jurnal Ekonomi Islam, 2022)
Pricing errors can have various consequences; unethical pricing can make entrepreneurs dislike buyers, and even buyers can give reactions that can damage the company's reputation. Unsolicited quotations from buyers may result in rejection by some or all purchasers. This study uses qualitative methods in observation, interviews, literature, and documentation. Based on the results of this study, it can be concluded that in setting the product selling price, the Family minimarket uses the Cost Plus Pricing method, the Family minimarket offers a set low price to achieve the target sales volume, sales value, and market share by minimizing profits. Therefore the Family minimarket implements the use of the odd pricing mechanism. And in determining the profit, the Family minimarket does not determine the upper and lower limits of the profit earned but only takes a margin of 10-15%.